THE EFFECTIVENESS OF PROBLEM BASED LEARNING USING CPS-THINKING FRAME ON CRITICAL THINKING ABILITY IN TERMS OF STUDENTS' SELF EFFICACY - Dewa Made Dwicky Putra Nugraha; Dewi Juniayanti (Jurnal Pendidikan Dasar Flobamorata, 2023)
This research aims at finding out the effectiveness of Problem Based Learning using CPS-Thinking Frame in terms of Self Efficacy on IV Grade students of SD No. 8 Benoa. This research was quasi-experiment. The design of this research was 2 x 2 factorial design. The population was IV Grade students of SD No. 8 Benoa amounted of 57 students with saturation sampling techniques; all population was taken as sample. The data analysis of hypothesis testing was two-way ANOVA using IBM SPSS 25 for Windows. The result shows F value = 73,976 with sig.= 0,000 or p 0,05; H0 is rejected and H1 is accepted. It shows that there is a significant difference on critical thinking ability between group with PBL using CPS-Thinking Frame and group with conventional method. The sig. value on intercept part is 0,000 or p 0,05; H0 is rejected and H1 is accepted. Thus, there is significant difference on critical thinking ability between students with high and low self-efficacy. It shows that students' self-efficacy has effect on critical thinking. Otherwise, learning model is uncorrelated to self-efficacy.